2018
DOI: 10.1111/jcpt.12744
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions during hepatitis C treatment with direct-acting antivirals: The role of medication errors, their impact on treatment discontinuation and their preventability. New insights from the Campania Region (Italy) spontaneous reporting syste

Abstract: This study found a proportion of preventable/potentially preventable ADRs involving DAA, which could be improved in the Campania Region (Italy). Additionally, the study identified a high proportion of seemingly unnecessary DAA discontinuations among patients who experienced ADRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(76 reference statements)
1
4
0
Order By: Relevance
“…In our study population, the prevalence of skin complaints and gastrointestinal effects was higher than that found by Villani et al in a recent meta-analysis [24]. Anemia was frequent in our population, which is typically associated with RBV use, similar to other studies [14,24,56]. In 47% of patients, RBV dose reduction or discontinuation was needed, which is a higher proportion of cases than reported by Conti et al [15].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In our study population, the prevalence of skin complaints and gastrointestinal effects was higher than that found by Villani et al in a recent meta-analysis [24]. Anemia was frequent in our population, which is typically associated with RBV use, similar to other studies [14,24,56]. In 47% of patients, RBV dose reduction or discontinuation was needed, which is a higher proportion of cases than reported by Conti et al [15].…”
Section: Discussionsupporting
confidence: 64%
“…However, as suggested by Hanlon et al, anticholinergic risk scales are easy and useful for identifying patients at risk of adverse effects, regardless of the scale used [41]. Sessa et al, found a proportion of preventable adverse drug reactions involving DAAs, suggesting that it would be a target for improvement [56]. Anticholinergic medications are a potentially modifiable risk factor for the prevention of adverse events and one may hypothesize that recognizing the use of anticholinergic drugs-and therefore potentially inappropriate polypharmacy-by means of these scales, could help in identifying older patients with comorbidities at risk of adverse events when starting antiviral therapy [57].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, doctors, followed by nurses and other health workers, represent the primary sources of spontaneous reports, especially in South Italy [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Several initiatives have been implemented, and others are still necessary to implement a pharmacovigilance culture among all healthcare professionals and the general population [ 32 , 33 , 34 , 35 , 36 , 37 ]. The pressure to which healthcare personnel have been subjected during the COVID-19 emergency is well known.…”
Section: Discussionmentioning
confidence: 99%
“…There is still no compelling evidence at present to sustain the conclusion that the use of DAAs for the treatment of HCV is associated with an increased risk of HCC occurrence [25,26]. Labelled DDIs of co-administered drugs were found to be the most common preventable criterion of ADRs related to DAAs [27]. It is known that especially the medicines that alter the activity of the enzymes CYP3A4 or CYP2C8 are contraindicated in patients treated with Om/Pa/Ri+Da [16].…”
Section: Discussionmentioning
confidence: 99%